2012
DOI: 10.1136/gutjnl-2012-303333
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptional analysis of the intestinal mucosa of patients with ulcerative colitis in remission reveals lasting epithelial cell alterations

Abstract: Objective Ulcerative colitis (UC) is a chronic condition characterised by the relapsing inflammation despite previous endoscopic and histological healing. Our objective was to identify the molecular signature associated with UC remission. Design We performed whole-genome transcriptional analysis of colonic biopsies from patients with histologically active and inactive UC, and noninflammatory bowel disease (non-IBD) controls. Real-time reverse transcriptase-PCR and immunostaining were used for validating select… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

19
198
3
2

Year Published

2013
2013
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 226 publications
(222 citation statements)
references
References 36 publications
19
198
3
2
Order By: Relevance
“…29 This suggests that low BRINP3 may identify a subgroup of patients within the general UC cohort and supports the previously reported heterogeneous genetic character of this disease. 53 Abnormal BRINP3 expression is specific for colonic mucosal tissue in UC and not a generic response to inflammation or therapy.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…29 This suggests that low BRINP3 may identify a subgroup of patients within the general UC cohort and supports the previously reported heterogeneous genetic character of this disease. 53 Abnormal BRINP3 expression is specific for colonic mucosal tissue in UC and not a generic response to inflammation or therapy.…”
Section: Discussionsupporting
confidence: 88%
“…21,22 Numerous studies have therefore been conducted in UC using both mucosal biopsies and surgical resection specimens. [21][22][23][24][25][26][27][28][29] In the vast majority of these studies, the samples were obtained from chronically inflamed tissue such that transcriptomic differences observed have been dominated by the consequences of tissue damage and the presence of infiltrating inflammatory cells. 21,24,26,27 A recent meta-analysis of a number of these studies 23 identified the tight junction molecule, claudin 8 (CLDN8), to be the most underexpressed gene in the colon in individuals with IBD.…”
mentioning
confidence: 99%
“…Previous studies have demonstrated different mRNA expression profiles of mucosal colonic biopsies from IBD patients and healthy individuals [34,35,46,47] . Furthermore, Olsen et al [34] demonstrated that active and inactive UC could be distinguished from CD patients and controls.…”
Section: Discussionmentioning
confidence: 99%
“…For instance, impaired butyrate oxidation has been associated with active mucosal inflammation. Apart from reduced butyrate oxidation itself, impaired butyrate uptake, most likely as a consequence of decreased MCT1 expression, was found in patients with active ulcerative colitis 45, 46. Moreover, density analyses from an open access genomewide association studies database revealed a dense cluster of associations for SLC16A7 (encoding for MCT2) variants with Crohn disease and high‐density lipoprotein (HDL) cholesterol levels, although functional validation is completely missing so far 47…”
Section: Mcts In Other Diseasesmentioning
confidence: 99%